PREVALENCE OF ALLERGIC DISEASE SYMPTOMS AMONG SCHOOL CHILDREN - Abdullaev N. Ch.; Urozaliev S. Yu. (Journals Park Publishing, 2024)
The article examines the prevalence of allergic disease symptoms among schoolchildren living in the Surkhandarya region of the Republic of Uzbekistan.
Keywords: allergic rhinitis, atopic dermatitis, bronchial asthma, symptoms, schoolchildren.